A Rare but Fascinating Disorder: Case Collection of Patients with Schnitzler Syndrome - Maaman Bashir; Brittany Bettendorf; Richard Hariman (Case Reports in Rheumatology)
Background. Schnitzler syndrome is a rare disorder characterized by a chronic urticarial rash and monoclonal gammopathy (IgM in more than 90% of the cases). It is difficult to distinguish from other neutrophilic urticarial dermatoses, and diagnosis is based on the Strasbourg criteria. Interleukin-1 is considered the key mediator, and interleukin-1 inhibitors are considered first line treatment. Here, we present two cases of Schnitzler syndrome, both successfully treated with anakinra. Objectives. To increase awareness regarding clinical presentation, diagnosis, and treatment of this rare disorder. Cases. We describe the clinical features and disease course of two patients with Schnitzler syndrome, diagnosed using the Strasbourg criteria. Both were treated with anakinra with remarkable response to therapy. Conclusion. Schnitzler syndrome is a rare and underdiagnosed disorder. High suspicion should be maintained in patients with chronic urticaria-like dermatoses, intermittent fevers, and arthralgias. A serum protein electrophoresis and immunofixation should be performed in these patients. The diagnosis is important to recognize as Schnitzler syndrome is associated with malignancy. A lymphoproliferative disorder develops in about 20% of patients at an average of 7.6 years after onset of symptoms. Thus, patients warrant long-term follow-up. IL-1 inhibitors are extremely effective in relieving symptoms and are considered first line therapy.